PENGARUH KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PERUMAHAN RAKYAT KABUPATEN KARANGANYAR - Purwanto, Setyo; Sukorina, Diana (Universitas Of Surakarta, 2024)
The Influence of Organizational Communication on the Performance of Public Works and Public Housing Department Employees in Karanganyar Regency. This was created to see and measure the existence of organizational obstacles which are characterized by problematic work patterns, including employees who ignore time discipline, decreased productivity, and conflicts between employees or with superiors which have an impact on work delays. Measuring the quality of relationships between employees which can influence comfort and well-being at work.This research aims to determine the effect of organizational communication on the performance of Karanganyar Regency Public Works and Public Housing Department employees. This research is quantitative research, the data collection technique uses a closed questionnaire, with 37 employees responding with statements. Data analysis uses simple linear analysis where the data source is processed using the SPSS statistical application.The research results show that there is a significant influence of organizational communication on employee performance, therefore the hypothesis can be proven. The R Square value is 59.2%. This value shows that organizational communication plays a role of 59.2% in employee performance in the work environment of the Karanganyar Regency Public Works and Public Housing Service. Meanwhile, there is still 40.8% which is influenced by other variables not examined in this research.